Turnings Fiji Factions - Lal, Brij V. (ANU Press, 2013)
Through Dr Lal's refreshingly clear and powerful prose and sharply observed stories, we enter the inner world of Indo-Fijian feeling and aspiration. One universal that emerges with particular clarity in the Indo-Fijian experience is the ceaseless struggle to find community in a changing world, balancing the beauty of ritual and tradition against the transcendent value of education and modern rationality. The volume poses the question of how people draw upon historical memory and immediate circumstances to create a social world, and how that world can be shared with others in multicultural society. The answer seems to lie somewhere between history and poetry, as in Dr Lal's 'factions.' - Andrew Arno University of Hawaii at Manoa, Honolulu